2022
DOI: 10.1371/journal.pone.0263072
|View full text |Cite
|
Sign up to set email alerts
|

“I just have to hope that this abortion should go well”: Perceptions, fears, and experiences of abortion clients in Nigeria

Abstract: This qualitative study aimed to examine how abortion clients in Nigeria perceive abortion and explore the role their beliefs and fears play in their care-seeking experiences and interactions with providers. Abortion is severely legally restricted in Nigeria but remains common. We conducted in-depth interviews with 25 people who obtained abortion services through three distinct models of care. We coded interview transcripts and conducted thematic analysis. Clients perceived negative attitudes toward abortion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 42 publications
(46 reference statements)
0
36
0
Order By: Relevance
“…In the absence of other influencing factors, women strongly preferred medically safe abortion methods and services [ 37 , 48 , 52 , 55 , 56 , 62 ]. Based on a study in Ghana, Esia et al [ 55 ] summarized that ‘ All the respondents indicated that they preferred to have abortion at recognized facilities and by recognized practitioners so as to make it safe ’ However, there was significant variation in what methods women perceived as most safe.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the absence of other influencing factors, women strongly preferred medically safe abortion methods and services [ 37 , 48 , 52 , 55 , 56 , 62 ]. Based on a study in Ghana, Esia et al [ 55 ] summarized that ‘ All the respondents indicated that they preferred to have abortion at recognized facilities and by recognized practitioners so as to make it safe ’ However, there was significant variation in what methods women perceived as most safe.…”
Section: Resultsmentioning
confidence: 99%
“…Women’s perceptions of the quality of care provided at facilities played a role in the decision-making process regarding where to seek abortion services [ 36 , 37 , 43 , 44 , 47 , 51 , 55 – 57 , 59 , 62 ] These perceptions included likelihood of respectful care and willingness of the provider to perform the requested procedure [ 33 , 34 , 57 ]. In Nigeria, perception of care had more to do with having a good reputation, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations